Ecopreneurship: A Sustainable Model As Entrepreneurship Education For Transformation - Shrestha, Narayan; Rijal, Madhu (Journal of Kathmandu BernHardt College, 2022)
Ecopreneurship is the process of using entrepreneurial skills and innovation to create sustainable solutions for environmental and social issues. It is a way to foster economic growth and peace through sustainable practices. Ecopreneurship can be used to promote sustainable development, alleviate poverty, and create employment opportunities. Ecopreneurship is a combination of two words ‘ecological (eco)’and ‘entrepreneurship’. Entrepreneurship is a part of the economy that is demanded in modern open economies. Structural changes in society are needed for the creation of entrepreneurship Entrepreneurship and more, particularly ecopreneurship, are essential to drive the sustainable transitions needed in educational sectors. Existing pedagogic frameworks should address these academic disciplines and they should be embedded in the educational curricula. The aim of this conceptual paper is to consider pedagogic and program design. This makes this paper of particular interest for academia, educational policymakers and education industry support sectors alike. An existing university that has both a student enterprise and ecopreneurship program and an established educational business incubator and accelerator is used as a case study to provide insight into how progress from ideation to commercialization can be more readily supported in a university setting. From a pedagogical perspective, it helps to develop new conceptual, methodological, and theoretically underpinned spiral pedagogies to teach and support colleges and universities as to how to exploit and take advantage of entrepreneurial and ecopreneur business opportunities. Ecopreneurship relates to environmentally friendly ways of doing business through school education systems.